Studying extent of smoking, alcohol consumption and other pyscho-active substance abuse among student of universities located at İstanbul - Tan Cömert, Itır; Ziyalar, Neylan (Journal of Dependence, 2010)
Objective: This study was conducted in order to examine extent of smoking, alcohol consumption and other pyscho-active substance abuse among students aged included in age group of 18-28 years who are living in Istanbul and are attending undergraduate, graduate and doctorate programs of a University located in Istanbul.Method: The study included 18-28 years old students living in İstanbul who are attending undergraduate, graduate and doctorate programs of Universities located in Istanbul. Present research constitutes a part of a doctorate degree study. This study was conducted by approving Approval no. 2006/392 dated 12.04.2006 of Ethics Committee, Cerrahpaşa School of Medicine. Field study was ended in December 2006. Size of sample was determined to include 600 individuals. Statistical processes were conducted by SPSS version 8.0.Results: Of participants of the study, 346 (57.7 %) were female and 254 (42.3 %) were male. When smoking behavior was examined (excluding pipe and cigar), it was observed that 25.5 % of sample (n=153) was regularly smoking in daily basis, 1.8 % n: 11) was regularly consuming alcohol in daily basis and 3.7 % (n: 22) were smoking marijuanaseveral times per month.Conclusion: Leaving families and home town at the end of adolescence and at the beginning of young adulthood to continue education in Istanbul, university students are under risk in terms of smoking, alcohol consumption and substance abuse. Within this context, university studies representing whole nation should be conducted in order to determine risks and thus, preventive effort should be made.
Keywords: Istanbul; University Students; Smoking; Alcohol; Psycho-active Substance